Practice of self-monitoring blood glucose among insulin-treated diabetic patients in Hospital Serdang - Zahari Sham, Siti Yazmin; Chellappah Thambiah, Subashini; Samsudin, Intan Nureslyna; Ng, Ooi Chuan; Yong, Shao Wei; Razmin, Nur Izzati (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Introduction: Diabetes Mellitus (DM), characterised by chronic hyperglycaemia, exposes patients to acute and chronic complications, such as hypoglycaemia and vascular complications, respectively. The latter is associated with the degree of glycaemic control. Glycated haemoglobin (HbA1c) indicates long-term glycaemic control of the preceding 2-3 months. The practice of self-monitoring blood glucose (SMBG) is essential for insulin-treated diabetic patients to achieve optimum glycaemic control and prevent hypoglycaemia. Aim: The study aimed to determine the SMBG practice and frequency and its association with HbA1c and factors in insulin-treated diabetic patients. Methods: This was a cross-sectional study of insulin-treated diabetic patients attending follow-up at the diabetic clinic of Hospital Serdang from April 2015 to August 2015. Consented eligible patients completed validated self-administered questionnaires. Patients’ HbA1c results were obtained from the hospital information system. Results: Ninety-one of 137 (66%) patients practiced SMBG and 46 (34%) did not. Although 82% had seen diabetic nurses, 54% of patients did not alter their treatment accordingly. Neither the practice nor the frequency of SMBG was significantly associated with differences in HbA1c levels (p=0.334 and p=0.116 respectively). Ethnicity and household income significantly affected SMBG practice. The presence and frequency of hypoglycaemia significantly increased the likelihood of SMBG practice (p<0.001) and frequency (p<0.001). Conclusions: The prevalence of SMBG practice in diabetic patients on insulin was 66%. However, SMBG was not followed by proper treatment alteration in 54% of patients. There was no association between SMBG practice and frequency with good glycaemic control. Hypoglycaemia significantly affected the practice and frequency of SMBG.